Climbing bean breeding for disease resistance and grain quality traits. Issue 2 (2nd September 2021) - Portilla, Ana Elisabeth; Mayor‐Duran, Victor Manuel; Buendia, Hector Fabio; Blair, Matthew W.; Cichy, Karen; Raatz, Bodo
Abstract: Common bean ( Phaseolus vulgaris ) is grown in two growth types, bush and climbing beans. The latter are preferred in several regions in East and Southern African as well as in Latin America (dominant in Rwanda and Colombia), due to higher yields and resilience compared with bush type. Common bean productivity is reduced by several pests and diseases between them. Bean common mosaic virus (BCMV), which is the most common and destructive poty‐virus affecting bean production worldwide, and anthracnose, caused by the fungus Colletotrichum lindemuthianum, can cause yield losses as high as 95% in susceptible cultivars. Further important traits in common bean are high micro mineral contents to alleviate malnutrition and grain quality traits such as the canning quality of bean varieties, which is important for farmers to access the processing market. In this study, new climbing bean populations were generated (coded ENF/CGA) to combine high seed iron (SdFe) and multiple diseases resistance. Double and triple crosses between parents with virus and anthracnose resistance, high SdFe, and good agronomic traits were employed. In trials in Darien and Popayan, lines were identified that combine BCMNV/BCMV and anthracnose resistance with seed yields above 4000 kg/ha. Phenotypic evaluations validated the usefulness of SNP markers tagging the genes bc‐3 and I for BCMN and Co‐3 for anthracnose as a selection tool for field resistance. These results show the genetic potential of the lines that are now being tested in target regions to be delivered to smallholder farmers.